Relevansi Pendidikan Kritis Paulo Freire Dengan Pendidikan Islam - Muhammad Zamroji (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2016)
Education represent process humanize human being which is plan and is continual. In Islam, education become system sub owning separate urgency in supporting intelectuality dimension and of spiritualitas Islam people. But reality that happened these days, frequently show education face which do not in line with principle of humanization. Education system which have there is and establish during the time can be pledged by as a